Reducing Diesel Exhaust Emissions By Optimisation Of Alcohol Oxygenates Blend With Diesel/Biodiesel - Hashim, Haslenda; Razak, Nurul Hanim; Yunus, Nor Alafiza (Elsevier Ltd, 2021)
Biodiesel is substantially found to reduce carbon dioxides, hazardous particulate matter but increasing anthropogenic nitrogen oxides (NOx) emissions. Fuel blending with alcohol oxygenate is one of the best NOx mitigation technologies. The objective of this present study is to develop a model-based product design optimisation of diesel/biodiesel/alcohol blends incorporated with an accurate NOx prediction model as the model's predictive accuracy. The compositions for each fuel blend are deliberately formulated via systematic Linear Programming. The effects of cetane number, oxygen content, and heat of vaporisation have been evaluated. Performance, combustion characteristics, and environmental impact of the fuel blends were compared to diesel standard, which complies with the fuel regulation: ASTM D975 and EN590 standards. The result depicted that 70% diesel, 20% biodiesel, and 10% butanol is the optimal blend with the similar performance (power output) as diesel, lowest cost, and NOx emissions reduction from 7% up to 15%. The increase of oxygen content causes a stronger cooling effect to reduce the NOx pollutant emissions. The NOx formation prediction has been performed by adopting the fuel blend properties, including cetane number, and oxygen content using a rigorous approach. The NOx formation prediction has been performed by adopting the fuel blend properties, including cetane number and oxygen content, using a rigorous approach. The final NOx prediction models developed can be a precursor to implementing the physical system in a dynamic testing phase. Higher alcohol (butanol) offers superior characteristics such as higher HOV (stronger cooling effect to reduce NOx formation), CV (higher power output), CN (reduces ignition delay), density and viscosity (better fuel flow for better atomisation), and flash point (for safer storage and handling) as compared to lower alcohol like ethanol. Conclusively, diesel/biodiesel/butanol enhances the HOV, which leads to a stronger cooling effect in the combustion chamber, thus reducing NOx formation.